Faktor-Faktor Yang Berhubungan Dengan Gangguan Menstruasi Pada Remaja Putri di SMAN 1 Tabanan - Sagitarini, Putu Noviana; Candra Citra Sari, Ni Made; Tri Agustini, Ni Komang; Ningrat Pangruating Diyu, Ida Ayu; Megayanthi, Sri Dewi (STIKES Ngesti Waluyo, 2024)
In adolescent girls, puberty is marked by the onset of menstruation, which is accompanied by physical, mental and social changes. Menstruation is a natural process that women usually experience, but this can become a problem if menstrual disorders occur. The high prevalence of menstrual disorders is caused by various factors such as stress, lifestyle, physical activity, medical conditions, hormonal disorders and nutritional status. This research aims to determine the factors associated with menstrual disorders in adolescent girls. This research uses a descriptive correlation design using a cross-sectional approach. The sampling method in this research uses probability sampling, namely stratified random sampling and simple random sampling at each level. The instruments used in this research were questionnaires and body mass index measurements. Data analysis was carried out univariate and bivariate using the chi-square test. The results of this study showed that age (p-value 0.859) and class (p-value 0.968) did not have a significant relationship with menstrual disorders in young women. Meanwhile, stress levels (p value 0.007), nutritional status (p value 0.033) and physical activity (p value 0.024) have a significant relationship with menstrual disorders in adolescent girls. It is hoped that the results of this research can become learning material and information for teenagers and avoid factors that can disrupt the menstrual cycle so that they can practice it in their daily activities.